Hydrogels and their role in bone tissue engineering: An overview - Jaisanghar Nallusamy; Raunak Kumar Das (Wolters Kluwer Medknow Publications, 2021)
An increasing incidence of the bone damage either due to trauma or a wide range of diseases related to bone necessitates the advent of new technologies or modification of the existing pattern of treatment to deliver utmost care to an individual thereby helping them to lead a normal and healthy life. Revolutionary changes in the field of tissue engineering (TE) pave a way from repair to regeneration of human tissues and restoring the health of an individual. Among the numerous biomaterials available, hydrogel emerges as a promising source of scaffold material in the field of bone TE (BTE). This article presents an overview on hydrogels and their role in BTE.